Seasonal influenza activity based on laboratory surveillance in Malaysia, 2011‐2016. Issue 3 (15th November 2018) - Sam, I‐Ching; Noraini, Wan; Sandhu, Sukhvinder Singh; Norizah, Ismail; Selvanesan, Sengol; Thayan, Ravindran; Yusof, Mohd Apandi; Hassan, Ardalinah; Jafar, Faizatul Lela; Chan, Yoke Fun
Abstract : Influenza seasonality in equatorial countries is little understood. Seasonal and alert influenza thresholds were determined for Malaysia, using laboratory‐based data obtained from the Malaysia Influenza Surveillance System and a major teaching hospital, from 2011 to 2016. Influenza was present year‐round, with no clear annual seasons. Variable periods of higher transmission occurred inconsistently, in November to December, January to March, July to September, or a combination of these. These coincide with seasons in the nearby southeast Asian countries or winter seasons of the northern and southern hemispheres. Changes in the predominant circulating influenza type were only sometimes associated with increased transmission. The data can provide public health interventions such as vaccines.